ЭРКИН АЪЗАМ КИНОҚИССАЛАРИ ТИЛИНИНГ ГРАММАТИК ЖИҲАТДАН ЎЗИГА ХОСЛИГИ - Холмуродова, М.И. (SCIENCE and SOCIETY, 2020)
The article describes the grammatical features of the language of Erkin A'zam's film stories, in particular, the description of the verbal expression of linguistic units. The sociopragmatic possibilities of some language units are also analyzed in the text of the film stories.
Keywords: text; sociopragmatic; grammatical meaning; lexical meaning; speaker; listener; author; grammatical task